2002
DOI: 10.1038/sj.cdd.4401051
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the balance between necrosis and apoptosis in human and murine cells treated with interferon and dsRNA

Abstract: Interferons enhance the cellular antiviral response by inducing expression of protective proteins. Many of these proteins are activated by dsRNA, a typical by-product of viral infection. Here we show that type-I and type-II interferons can sensitize cells to dsRNA-induced cytotoxicity. In caspase-8-or FADD-deficient Jurkat cells dsRNA induces necrosis, instead of apoptosis. In L929sA cells dsRNA-induced necrosis involves high reactive oxygen species production. The antioxidant butylated hydroxyanisole protects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
83
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 67 publications
4
83
0
Order By: Relevance
“…1,2 The same rationale led to the conclusion that ROS were also involved in dsRNA-induced necrosis of L929 cells. 3 Nevertheless, here we show that although BHA and BHT differ only slightly in their ability to reduce the levels of ROS induced by TNF stimulation of L929 cells, BHA is clearly more antinecrotic than BHT in this necrotic cell death system (Figure 1b). Both BHA and BHT reduce ROS levels and necrosis of L929 cells after stimulation with dsRNA ( Figure 1c).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…1,2 The same rationale led to the conclusion that ROS were also involved in dsRNA-induced necrosis of L929 cells. 3 Nevertheless, here we show that although BHA and BHT differ only slightly in their ability to reduce the levels of ROS induced by TNF stimulation of L929 cells, BHA is clearly more antinecrotic than BHT in this necrotic cell death system (Figure 1b). Both BHA and BHT reduce ROS levels and necrosis of L929 cells after stimulation with dsRNA ( Figure 1c).…”
mentioning
confidence: 61%
“…However, BHA apparently does not block dsRNA-induced cytotoxicity, but shifts cell death from necrosis to apoptosis, whereas BHT does not modulate cell death type (Figure 1d). 3 Together, these data imply that BHA possesses additional properties that make it a more potent antinecrotic agent than BHT.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…12 When the treated cells were deficient for FADD or caspase-8, or when treatment was carried out in the presence of the pancaspase inhibitor benzyloxycarbonyl-Val-Ala-DL-Asp(OMe)-fluoromethylketone (zVAD-fmk) cells responded by rapid necrosis. 12 Treatment of Jurkat E (JE) and JB6 Jurkat cells with dsRNA (100 mg/ml poly I:poly C), rapidly induced cell death (Figure 1). The morphology of dying JE cells treated with either anti-Fas or dsRNA was typically apoptotic (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…11 We have shown that in addition to increasing the capacity of cells to resist viral infection, type-I and type-II interferons can sensitize cells to external dsRNA-induced apoptosis and necrosis and demonstrated that dsRNA induced apoptosis but not necrosis requires FADD and caspase-8. 12 In addition to eIF2-a phosphorylation and inhibition of translation, PKR is involved in regulation of the activation of several transcription factors such as NF-kB, p53, or STATs.…”
mentioning
confidence: 99%